X-Ray-Induced Changes to Passivation Layers of Lithium-Ion Battery Electrodes - Benjamin T. Young; David R. Heskett; Joseph C. Woicik; Brett L. Lucht (Journal of Spectroscopy)
The surface sensitivity available to photoelectron spectroscopies (PESs) makes them popular techniques for characterization of chemical environments at shallower depths than other, more bulk-sensitive techniques and because they are generally thought to be nondestructive. Variable energy, synchrotron radiation (SR), permits access to information not available to common lab-based radiation sources, making high-energy PES studies extremely useful for understanding thin films and interfaces. High-SR photon flux has been useful for developing models of soft X-ray-induced effects, but hard X-ray SR-induced effects are less well studied and will be increasingly important as popularity and availability of SR for thin film analysis continues to grow. We report here on observed modification of the solid electrolyte interphase of a lithium-ion battery electrode during prolonged exposure to 4 keV SR. The effects can be summarized by desorption of oxygen-containing species from the sample surface and by reactions within the film. Also presented is an estimate of the layer thickness’ time evolution during the prolonged SR exposure.